AKUNTABILITAS DAN TRANSPARANSI PENGELOLAAN DANA DAERAH PADA INFRASTRUKTUR JALAN RAYA JIWAN - Muhammad Akbar Akbar; Zaskia Nuha Zaskia; Indra Devian Lumban Gaol (Badan Perencanaan Pembangunan Daerah Provinsi Banten, 2026)
This study is based on the importance of applying accountability and transparency principles in managing local funds for road infrastructure development in Jiwan District, Madiun Regency, where various governance challenges are still encountered in practice. This study aims to examine the level of accountability and transparency implementation and to identify factors influencing the effectiveness of fund management. A qualitative descriptive approach was employed, with data collected through in-depth interviews with eight key informants, field observation, and documentation study, analyzed using Miles and Huberman's interactive analysis model. Data validity was tested through source and method triangulation. The findings reveal that administratively, the management of funds has fulfilled vertical accountability requirements through routine reporting to the DPUPR and inspectorate; however, horizontal accountability remains suboptimal due to the community's extremely limited involvement throughout the entire budget cycle. Furthermore, transparency has not been fully implemented, as indicated by the absence of project information boards in the field, non-publication of budget documents, and minimal public participation forums. These conditions result in a discrepancy between financial realization at 92% and physical achievement at only 78% of the 2024 target. This study contributes theoretically by confirming the accountability gap model in the context of road infrastructure at the sub-district level, while recommending strengthened e-government-based reporting systems, enhanced community participation, and improved external oversight mechanisms.